#150 : Do Women with a History of Recurrent Miscarriage Have a Higher Risk of Obstetric and Perinatal Complications in a Subsequent Pregnancy? A Cohort Study - Xiaoyan Chen; Tin Chiu Li (Fertility & Reproduction, 2023)
Background and Aims: To examine if there are any adverse obstetric and perinatal outcomes associated with a history of recurrent miscarriage (RM) among a large cohort of Chinese women in Hong Kong. Method: It is a retrospective study using prospectively collected data from 2000 to 2019. Data of obstetric and perinatal outcomes from 3112 women with history of recurrent miscarriage was collected from the Clinical Data Analysis and Reporting System database and compared to 108,012 deliveries within the same time period. Logistic regression analyses were performed, adjusting for potential confounding factors. Results: For obstetric outcomes, women with RM had significantly increased odds of gestational hypertension (OR 1.28, 95% CI 1.09-1.51) and Caesarean section (OR 1.47, 95% CI 1.36-1.60). After adjusting confounding factors, there was significantly increased odds for only Caesarean section (adjusted OR 1.55, 95% CI 1.32-1.77). For perinatal outcomes, women with a history of RM were more likely to deliver preterm (OR 1.67, 95% CI 1.47-1.91; adjusted OR 1.72, 95% CI 1.50-1.99). The incidence of small for gestational age was also significantly higher in women with a history of RM (OR 1.64, 95% CI 1.39-1.94; adjusted OR 1.70, 95% CI 1.41-1.98). There was a significant difference in the incidence of perinatal death from all causes (OR 1.48, 95% CI 1.03-2.12; adjusted OR 1.52; 95% CI, 1.11-2.32). Conclusion: An increased risk of several obstetric and perinatal complications was found in a large cohort of Chinese women with a history of two or more miscarriages, who should be offered specialist obstetric care from the start of pregnancy with an emphasis on strategies to manage the increased risk of preterm birth small for gestational age and perinatal death.